Factor Affecting the Outstanding Debt on Poverty Loan of Nayoby Bank, Parkseang Service Unit, Luang Prabang Province - PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The rural development has a strong link to poverty reduction through implementation of the 3-builds directive in Lao PDR and it is the Nayoby bank’s job. Therefore, Poverty Loan of Nayoby bank has played significant role to resolve the Poverty in Lao PDR and Poverty Loan provision has been increasing day by day. The Credit of Nayoby bank also increases the outstanding debt as well. So that, this research aims to resolve the outstanding debts on the bank system. The Research utilized a survey method, collected data from the debtors for Poverty Loan of Nayoby Bank Parkseang service unit, Luang Prabang Province and use statistics program to analyze the Logistics Regression. The research results shows that the number of customers got the loan from Policy Bank at Parkseang district, Luangprabang province is 200 families. It’s one poverty district in Luangprabang. All most customers got the loan from Policy Bank is long term, the purpose for agriculture and some customers got the loan for run their new business. The amount of loan is between 10,000,000 to 20,000,000 Kip. They must return money to the bank in 5 years and pay in cash 500,000 Kip per time. Before they got the loan from the bank they have to have collaterals to show such as land or house. We can discover that 79% of customers have outstanding debt and the debt is in arrears around 5,000,001-10,000,000 Kip. Factors affecting the outstanding debt on Poverty Loan of Nayoby Bank, Parkseang Service unit, Luang Prabang Province consist of five factors such as: local economy downturn. Some bank officers’ behavior in Debt collection is inappropriate. Some customers didn’t follow the rule and the purpose of the bank. Health problem and debt burden is getting increased had statistical significance at the level of 0.1.